Dynamics of clinical disease prevalence at cattle farm in Bangladesh Livestock Research Institute, Savar, Dhaka, Bangladesh from 2011 to 2014 - Munsi, Md Nuruzzaman; Yousuf, Md Abu; Hossain, Sheikh Mohammad Jahangir (Asian Journal of Medical and Biological Research, 2015)
Bangladesh Livestock Research Institute (BLRI) plays an important role of public service to animal welfare since the period of 1984. There are a lot of cattle with their proper records in this Institutes cattle farm but previously no report regarding the dynamics of disease prevalence was published. So this research was conducted to determine the prevalence of clinical diseases and manifestations of cattle recorded and breed susceptibility to such diseases in different seasons during the period of January 2011 to December 2014. A total of 1558 cattle (where Pabna was 906 and Red Chittagong Cattle was 652) were included under this study. Diagnoses of clinical diseases and disorders were based on clinical history, clinical findings and different laboratory tests. Among the clinical cases, the highest prevalence was determined in case of ring worm (3.11%) followed by diarrhoea (1.86%), bovine ephemeral fever (1.08%), pneumonia (0.96%), alopecia (0.81%), mange (0.37%), tympany/bloat (0.69%), fever (0.64), lameness (0.53%), arthritis (0.40%), mastitis (0.39%), malnutrition (0.26%) and posthitis (0.19%). Infectious diseases like foot and mouth disease (FMD), black quarter (BQ), anthrax and haemorrhagic septicemia (HS) were not found which may be due to regular vaccination and maintenances of strict biosecurity. In case of breed, higher prevalence (12.09%) was found in Red Chittagong Cattle (RCC) compared to Pabna (11.13%). Among the seasonal cases, winter season (5.21%) had higher prevalence than rainy season (2.26%) followed by summer season (1.65%) in case of RCC, while summer season (3.85%) had higher prevalence than winter season (3.74%) followed by rainy season (3.30%) in case of Pabna. It may be concluded that several diseases and disorders occurred in the BLRI cattle farm but major infectious diseases did not take place owing to improved management of the farm. Asian J. Med. Biol. Res. June 2015, 1(2): 350-358